the PENGARUH PERENCANAAN LOGISTIK TERHADAP EFEKTIVITAS MANAJEMEN LOGISTIK FARMASI DI RUMAH SAKIT DR. BRATANATA JAMBI: PENGARUH PERENCANAAN LOGISTIK TERHADAP EFEKTIVITAS MANAJEMEN LOGISTIK FARMASI DI RUMAH SAKIT DR. BRATANATA JAMBI - Aulia, sarah Nasywa; Irawan, Yeyen Gustina; Sitepu, Fransiska; Pordaningsih, Reny; Riama, Apni (ARUMAS, 2025)
Logistics management is part of the supply chain process and has functions, namely planning, implementing, and controlling the efficiency and effectiveness of the flow of storage of goods, services, and service information and providing related information from the initial place or consumption. The hospital pharmacy installation is one part of the hospital that is fully responsible for drug management and an important factor that must be considered in providing equitable health services to the community in the hospital's work area. The purpose of drug management is to ensure the availability, distribution, and affordability of drugs with sufficient types and quantities, so that they can be easily obtained at the right place and time. This study aims to determine how the pharmaceutical logistics planning system carried out and identify the influence of planning on the effectiveness of pharmaceutical logistics management at dr. Bratanata Hospital, Jambi. The research method used is qualitative. Samples were taken using purposive sampling techniques of 3 people. Data collection techniques use Data Source Triangulation, namely in-depth interviews, observations, and documentation studies. The results of the study indicate that Pharmaceutical Logistics planning is carried out by referring to doctor requests, previous month's usage data, and the National Formulary. The planning process is based on a monthly stock opname system, where the remaining stock from January to December is added up, averaged, and added with a buffer stock of 10% for annual needs. Overall, the pharmaceutical logistics planning system at dr. Bratanata Hospital, Jambi has been running effectively, although flexibility is still needed in procurement to anticipate dynamic changes in hospital service needs and to ensure that all incoming and outgoing goods recording processes can be properly documented as a basis for decision making in logistics management.